Primary anaplastic large T-cell lymphoma of the psoas muscle - Pecorella, Irene; Ferrari, Angela; Tornese, Andrea; Lai, Quirino; Mennini, Gianluca; Rossi, Massimo (Polish Journal of Pathology, 2021)
Lymphomas presenting and mimicking soft-tissue masses are important to recognize, to avoid unnecessary treatment delays or extensive surgery. We describe a case of primary anaplastic large cell lymphoma (ALCL) arising from a deep skeletal muscle in a middle-aged male. He presented with a two-month history of swelling of his right thigh and mild fever, which led to a diagnosis of abscess formation. Antibiotics were prescribed for two weeks, with little improvement of symptoms. Subsequently, an exploratory surgery, with excision of the mass, demonstrated a ALCL of the psoas muscle, ALK-1 positive.